Reading and writing, singing and playing on three early red-figure vases - Pöhlmann, Egert (Greek and Roman musical studies, 2019)
The tools for reading and writing, the writing tablets and the papyrus scroll, were inherited by Greece from the East together with the Phoenician alphabet. The oldest papyrus scroll and writing tablets with Greek text were found in the tomb of a musician in Daphne dated to 430 BC. After 700 BC writing tablets were ubiquitous in Greece. However, black figure vases do not depict them. The first writing tablet appears on a red figure kylix of the Euergides Painter from Vulci (520). The first papyrus scrolls appear, together with writing tablets and the lyre, on a kylix from Ferrara (c. 480-70). Papyrus scrolls, writing tablets, the lyre and aulos appear together on the famous Berlin kylix of Douris from Caere (480).
CRIS-Team Scopus Importer:2024-12-16
Keywords: Early red-figure vases; Oral teaching of music; Papyrus scroll; Teaching of poetry and prose by reading and writing; Writing tablet